International commercial courts : the future of transnational adjudication - Brekoulakis, Stavros L.; Dimitropoulos, Georgios, 1984- (Cambridge : Cambridge University Press, 2022)
The book offers a comprehensive analysis of the role, importance and place of international commercial courts in the field of international adjudication from a comparative perspective. In a time where scholarly and academic debates revolve around the issues of the role of law in the post-globalization era, the new international commercial courts seem to be in the position to bridge concerns regarding diminished sovereignty, on the one hand, and the necessity of globalizing dispute resolution, on the other. International commercial courts thus present themselves as the paradigm for the future of adjudication.
Christopher Grout, Registrar, Qatar International Court & Dispute Resolution Centre and Sir William Blair, Judge, QICDRC / The role of international commercial courts in commercial dispute resolution -- Thomas Schultz, Professor of Law, King's College London, and SNF Research Professor of International Law, Graduate Institute of International and Development Studies, Geneva, and Clement Bachmann, Graduate Institute of International and Development Studies, Geneva / International commercial courts : possible problematic social externalities of a dispute resolution product with good market potential -- Christopher Vajda, Barrister, Moncton Chambers / Transnational adjudication and the court of justice of the European Union -- Ilias Bantekas, Professor of Law, HBKU Law, Lessons for International Commercial Courts from the Experience of the Proliferation of International Criminal Tribunals -- Janet Walker, Professor of Law, Osgoode Hall Law School / A comparative perspective to international commercial courts : jurisdiction, applicable law, and enforcement of judgments --Eva Lein, Professor, University of Lausanne, and Senior Research Fellow in Private International Law, BIICL / Jurisdiction and choice of court clauses in favour of international commercial courts -- Man Yip, Associate Professor of Law, Singapore Management University School of Law / The battle for jurisdiction through jurisdictional requirements : comparing between the 8 Chinese international commercial courts, the Singapore International Commercial Court, and the commercial court of England and Wales -- Mateja Durovic, Reader in Contract and Commercial Law, King's College London, and Franciszek Lech, KURF Research Assistant, King's College London / Harmonization of commercial law based on the common law : the role of international commercial courts -- Faris Elias Nasrallah, Solicitor, Senior Courts of England and Wales, and Researcher in International Arbitration, Max Planck Institute for Social Anthropology / Applicable laws in the International commercial courts of the Gulf -- Georgios Dimitropoulos, Associate Professor of Law and Associate Dean for Academic Affairs, HBKU Law / The design of international commercial courts : from organizational hybridity to functional interoperability -- Marieke Witkamp, Judge, Court of Rotterdam / Internationalizing domestic courts in Europe : a comparative analysis on procedure, function, organization -- Catherine A. Rogers, Professor of Law, PennState Law and Bocconi University, and Professor of Ethics, Regulation and the Rule of Law, Queen Mary University of London / The legitimacy and ethics of international commercial court judges -- Zachary R. Calo, Professor of Law, HBKU Law / Counsel ethics in transnational lawyering : the case of international commercial courts -- Pietro Ortolani, Professor of Digital Conflict Resolution, Radboud University / The use of technology at international commercial courts -- Julian Bailey, Partner, White & Case / The interplay between international commercial courts and ordinary courts -- Michael Patchett-Joyce, Barrister,The 36 Group / Private autonomy in international commercial dispute resolution : international commercial arbitration and international commercial courts -- Georgia Antonopoulou, PhD Candidate, Erasmus School of Law / Procedure before international commercial courts and ordinary courts : a comparative perspective -- Salvatore Caserta and Mikael Rask Madsen, Director of iCourts, Copenhagen / Hybridity in international adjudication : how international are international commercial courts? -- Julien Chaisse, Professor of Law, City University of Hong Kong, and Xu Qian, Senior Research Fellow, Faculty of Law, Chinese University of Hong Kong / The China international commercial court : architecture, pitfalls, and promises -- The Rt. Hon. The Lord Woolf CH and Christopher Campbell-Holt / The emergence of international commercial courts and dispute resolution centres in frontier markets : a perspective from Kazakhstan -- Geert Van Calster, Professor of Law, and Head of the Institute of Private International Law, KU Leuven / Brexit and the competition of dispute resolution fora in Europe : whither the rush to English courts post withdrawal? -- Susan L. Karamanian, Dean, HBKU Law / international commercial courts, dispute resolution, and the rule of law.
Title from publisher's bibliographic system (viewed on 07 Apr 2022).
Keywords: Commercial courts; Commercial law; Dispute resolution (Law)